An examination of organisational policies for healthcare and lifestyle decision‐making among Australian aged care providers. (8th September 2019) - Sinclair, Craig; Field, Sue; Blake, Meredith; Radoslovich, Helen
Abstract : Objective: Examine policies of aged care organisations relating to healthcare and lifestyle decision‐making. Methods: Seven aged care organisations submitted policy documents. Policies were analysed using the Australian Law Reform Commission (ALRC) "Decision‐Making Principles" as a framework. Senior staff (N = 9) with policy development roles participated in follow‐up interviews. Results: The structure and content of policy documents varied significantly between organisations. Most acknowledged the need to support the rights of care recipients in decision‐making; however, the nature of this support was often unclear. Interview themes included factors relating to "organisational contexts" "policy development and implementation" and "ethical challenges." An overarching theme among high‐performing organisations was "proactive response aimed at pre‐empting decision‐making dilemmas". We provide recommendations for policy development, including a self‐assessment audit tool. Conclusion: Aged care provider organisations may need to review policies in the areas of healthcare and lifestyle decision‐making to meet current best practice principles.